Rebuilding social democracy core principles for the centre left - Hickson, Kevin 1974- (Policy Press shorts, 2023)
The British Labour Party could hardly be more obviously in crisis. Though the party held power from 1997 to 2010, at the end of that period it was intellectually exhausted, and its opposition to the coalition government and the subsequent Conservative government was largely ineffective. This book aims to fix that, offering a clearly defined set of aims and values that the Labour Party can use to rebuild itself and the nation